The impact graphical user interface in game design elements of a mobile augmented reality (MAR) platform with a game-based approach zapworks tool to improve diploma students’ design skills in creative multimedia technology (CMT) of higher education / Fasehah Abdullah - Abdullah, Fasehah (2024)
Qualitative thematic analysis for graphical user interface as in game design elements of a mobile augmented reality (MAR) platform to discover and analyse 12 respondents’ responses as primary data collection and meta-analyses from previous researchers and current MAR game designs as secondary data collection. The significance of this research is to assist AR beginners or students at the Diploma in Higher Education level to create a positive impact when designing their initial MAR games based on their understanding and practical design skills at the Body of Knowledge (BOK) level. The main problems of this research it is essential to analyse appropriate fundamental graphical user interfaces as in game design elements for mobile augmented reality games, especially students at the Diploma level in Higher Education, in order to complying with MQA Programme Standard. The research aimed to bridge the gap between elements such as interactivity, functionality, bugs and errors, and selection of design elements in generating MAR games using AR development tools such as AR Toolkit and ZapWorks platforms, especially for amateurs, and this aimed to align with the research objectives of this research. Qualitative thematic analysis was performed using purposive sampling to obtain primary and secondary data with the assistance of NVivo instruments, including primary data collected from four different batches focus groups due to most of private institution combines all different batches in one class with same assignment brief and rubrics, and additionally, secondary data from meta-analyses and systematic reviews conducted by previous researchers and established MAR games. The results of the data collection revealed that the most suitable AR development tool that can help students improve their design skills when creating MAR games is ZapWorks. In addition to that, the results show that the design sample of the graphical user interface consistently utilised only four GUI elements, including 2D graphic design, 3D models, text, audio or sound, and video elements. Meanwhile, the data collection results revealed that the design sample for suitable criteria in game design elements consistently utilised only three design elements, namely level, point, and score. The conclusions drawn from these findings will serve as fundamental guidelines for students and particularly educators when incorporating these findings into their lesson plans (Course Learning Outcomes, CLO). Moreover, this evaluation instrument can be utilised in the Creative Multimedia Technology (CMT) BOK to assess Game Art areas for beginners at the Diploma level in MAR game creation. For future recommendations, this course be implemented in MOOCs and micro-credentials are innovative learning platforms for online students. Next, highlighted in the new enhancement of Bartle theory for AR beginners’ guidelines to create MAR game such as Achievers and Killers in levels, points, and scores for game design elements, and additionally, incorporating elements for Explorers and Socialisers in text, video, audio, sound, and video within the graphic user interface.